Leverage and litigation risk on profit management and profitability as mediation in manufacturing companies - Evi Maulida Yanti; Rusydi Rusydi; Husaini Abdullah (Institute of Computer Science (IOCS), 2023)
This research was conducted on Transportation Sector Manufacturing Companies listed on the Indonesia Stock Exchange 2015-2022 with a population of 80 elements. This research uses secondary data using SmartPLS as a data processing tool. The aim of this research is to see whether leverage and litigation risk have an effect on profitability and earnings management and to find out whether profitability is able to mediate the effect of leverage and litigation risk on earnings management. The research results show that 1) leverage has no effect on profitability, 2) litigation risk has no effect on profitability, 3) leverage has no effect on earnings management, 4) litigation risk has no effect on earnings management, 5) profitability has no effect on earnings management, 6 ) profitability is not able to mediate the effect of leverage on earnings management, 7) profitability is not able to mediate the effect of litigation risk on earnings management